2015
DOI: 10.1093/abbs/gmu112
|View full text |Cite
|
Sign up to set email alerts
|

The non-canonical Hippo/Mst pathway in lymphocyte development and functions

Abstract: The canonical Hippo/Mst pathway, originally discovered in Drosophila, is famous for its function in promoting apoptosis, inhibiting cell proliferation and tumorigenesis, and regulating tissue regeneration. However, emerging evidence shows that multiple non-canonical Hippo signaling pathways are also implicated in the regulation of various other biological processes. Recent studies have revealed that Mst1/2, the core kinases of Hippo/Mst pathway are required for T cell development, function, survival, trafficki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…In this perspective, the Hippo pathway, a key regulator of immunological homeostasis appears to influence significant steps during initiation or progression of various patho-physiological conditions31. Interestingly, role of Hippo signaling during mycobacterial infection of the host immune cells and subsequent manifestations towards disease progression is not known.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective, the Hippo pathway, a key regulator of immunological homeostasis appears to influence significant steps during initiation or progression of various patho-physiological conditions31. Interestingly, role of Hippo signaling during mycobacterial infection of the host immune cells and subsequent manifestations towards disease progression is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Originally identified in Drosophila to promote apoptosis24, inhibit cell proliferation and tumorigenesis2325; Hippo signaling components are now being implicated in T-cell deficiency associated with viral, bacterial and fungal infections26272829 and also in autoimmune manifestations30. MST1/2 deficient mice were reported to have hypoplastic lymphoid organs because of defective T cell migration3031. It was also shown that MST2 deficient mice produce decreased levels of proinflammatory cytokines and chemokine CCL2 during the process of retinal detachment32.…”
mentioning
confidence: 99%
“…In the context of the immune system, a non-canonical, Hippo/MST pathway is emerging as a central orchestrator of T cells activities, being implicated in an array of functions spanning from T cells development and activation to survival and trafficking. 13 Another level of regulation of core Hippo kinases refers to their cooperation with central nodes of the DNA damage response (DDR) machinery, chiefly the ataxia telangiectasia and Rad3-related protein (ATR)-Checkpoint kinase 1 (Chk1) and ataxia telangiectasia mutated (ATM)-Checkpoint Kinase 2 (Chk2) signaling avenues.…”
Section: Introductionmentioning
confidence: 99%
“…This results in the cytoplasmic sequestration and degradation of YAP/TAZ, which inhibits YAP/TAZ-driven cell proliferation, survival, and migration. NDR1/2 are newly identified as members of the Hippo pathway (5,18,27), and were reported to play similar roles like LATS1/2 as upstream kinases of YAP (28)(29)(30)(31)(32)(33). Recent studies demonstrated critical functions of the Hippo signaling in innate immunity (17,24,34).…”
Section: Introductionmentioning
confidence: 99%